2020
DOI: 10.1038/s41598-020-65372-8
|View full text |Cite
|
Sign up to set email alerts
|

Nyctinastic thallus movement in the liverwort Marchantia polymorpha is regulated by a circadian clock

Abstract: The circadian clock coordinates an organism's growth, development and physiology with environmental factors. One illuminating example is the rhythmic growth of hypocotyls and cotyledons in Arabidopsis thaliana. Such daily oscillations in leaf position are often referred to as sleep movements or nyctinasty. Here, we report that plantlets of the liverwort Marchantia polymorpha show analogous rhythmic movements of thallus lobes, and that the circadian clock controls this rhythm, with auxin a likely output pathway… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…It is well established that auxin affects growth in plants (see for example the reviews [ 40 , 41 ], and references therein), and we have previously shown that auxin levels in wild-type M . polymorpha gemmalings show a clear circadian rhythm in LL conditions [ 32 ]. However, in Mp lux ge lines, auxin levels are higher, arrhythmic and increasing with time in LL [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that auxin affects growth in plants (see for example the reviews [ 40 , 41 ], and references therein), and we have previously shown that auxin levels in wild-type M . polymorpha gemmalings show a clear circadian rhythm in LL conditions [ 32 ]. However, in Mp lux ge lines, auxin levels are higher, arrhythmic and increasing with time in LL [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the non-vascular land plants, the liverwort Marchantia polymorpha has recently emerged as a model species with low genetic redundancy among regulatory genes, simplifying genetic approaches [ 27 ]. Many molecular tools are available for genome editing and loss- and gain-of-function analyses [ 28 31 ], as well as tools for studying growth and clock output [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1c,d). Molecular studies of the liverwort Marchantia polymorpha revealed characteristics of a circadian oscillator, as gene expression and thallus movement were rhythmic under constant light (Lagercrantz et al ., 2020). However, they appear to have lost the CCA1/LHY/RVE homolog and instead possess a single RVE3,4,5,6,8‐like homolog (Linde et al ., 2017) (Fig.…”
Section: The Origins Of Clock‐mediated Abiotic Stress Response In the Green Lineagementioning
confidence: 99%
“…M. polymorpha is thought to have diverged from flowering plants about 400 million years ago (Delwiche and Cooper 2015, Kohchi et al 2021), with liverwort-like plants occurring earlier in the fossil record than other land plant forms such as vascular plants (Edwards et al 1995). M. polymorpha is a useful model to investigate questions concerning the evolution of circadian regulation because it has a circadian oscillator that shares some components with flowering plants (Lagercrantz et al 2021, Linde et al 2017), there is circadian regulation of a subset of the transcriptome and the position of its thallus lobes (Lagercrantz et al 2021, Lagercrantz et al 2020), and it can be used in experimental designs comparable to models such as Arabidopsis. Whilst circadian rhythms and some aspects of circadian clock structure have been identified in M. polymorpha , it is not yet known whether the regulation of photosynthesis represents a conserved output from its circadian system.…”
Section: Introductionmentioning
confidence: 99%